Virtual Learning in Indonesia's First Secondary School: To Anticipate Learning Loss - Farhan Ferian; Sudrajat Sudrajat (AL-ISHLAH: Jurnal Pendidikan, 2022)
Some research results state that the impact of implementing learning during the COVID-19 pandemic is in the form of online learning, one of which is learning loss. The purpose of the study is to provide notes on online learning in Indonesia that in addition to focusing on learning, one must also be able to anticipate learning loss. This study uses a literature study method by selecting various research articles that are in accordance with the research study. The results of the research state that indeed online learning will have an impact in the form of learning loss and in this research it also provides solutions in resolving learning loss through more intense communication from teachers and parents and maximizing teacher activities in learning so that they can anticipate learning loss so as to achieve learning goals. such as: online learning using a platform that is student-friendly and comfortable to use by students so that students can study at home to the maximum and parental control must always be done because learning takes place at home. The results of this study are expected to be able to anticipate learning loss, inspire parents and teachers to be able to take the importance of online learning for students.